THE IMPLEMENTATION OF THE POLITICS OF MEMORY: REGIONAL DIMENSION (example of Ivano-Frankivsk) - Венгринюк, Л. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Article is devoted to the implementation of politics of memory at the regional level. Based on the analysis of local space labeling and commemorative practices considered local governments in the area of the politics of memory. Analyzed the process of ideological decolonization of the memory from Soviet past which is realised by destruction or redefinition the most visible symbolic markers.